HUBUNGAN ANTARA FREKUENSI KUNJUNGAN KE PERPUSTAKAAN DENGAN PRESTASI BELAJAR PAI PADA SISWA KELAS VIII SMP NEGERI 2 PANJATAN KULON PROGO YOGYAKARTA - Hanif Cahyo Adi Kistoro; Wachdiati Wachdiati (Jurnal Pendidikan Agama Islam, 2017)
In structure of national education curriculum, subject PAI is a compusory subject, as well as civic education subjects, mathematics, social and culture. It has a high achievement in PAI subject matter is very important. One that supports high learning achievement of PAI is visits to the library. This study aims to test whether there is a correlation between frequency of visits to library with learning achievement of PAI. Subject in this study were students of SMPN 2 Panjaitan Kulonprogo Yogyakarta as many as 131 students. Data collection was done by using document rapports to reveal learning achievement of PAI and frequency to visits library from students visit to school library card. Results show that there is no correlation between frequency to visits school library with learning achievement of PAI with r = 0,104 and significancy p=0,119 (p>0,005).